2010
DOI: 10.1186/1476-4598-9-238
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 4 loss increases tumor cell invasion and is regulated by miR-21 in oral squamous cell carcinoma

Abstract: BackgroundThe tumor suppressor Programmed Cell Death 4 (PDCD4) has been found to be under-expressed in several cancers and associated with disease progression and metastasis. There are no current studies characterizing PDCD4 expression and its clinical relevance in Oral Squamous Cell Carcinoma (OSCC). Since nodal metastasis is a major prognostic factor in OSCC, we focused on determining whether PDCD4 under-expression was associated with patient nodal status and had functional relevance in OSCC invasion. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 49 publications
5
103
1
2
Order By: Relevance
“…In a similar previous study on the expression of miRNAs, mir-21 was significantly up-regulated in BC (Iorio et al, 2005). Our data are consistent with other reports indicating that mir-21 expression increased with advanced clinical stage Reis et al, 2010) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In a similar previous study on the expression of miRNAs, mir-21 was significantly up-regulated in BC (Iorio et al, 2005). Our data are consistent with other reports indicating that mir-21 expression increased with advanced clinical stage Reis et al, 2010) .…”
Section: Discussionsupporting
confidence: 82%
“…Down-regulation of PDCD4 at both the mRNA and protein levels significantly associated with regional disease, more advanced tumor stages, and poorer survival . (Reis et al, 2010). In the present study there was downregulation of PDCD4 in the breast cancer tissues compared to the adjacent non-neoplastic tissues and was associated with the increase in the expression of mir-21.…”
Section: Discussionmentioning
confidence: 52%
“…Studies have revealed differential expression of several genes in OSCC lesions such as cyclin D1, EGFR, Tetranectin, NuclearS100A7, Smad2, Smad6, DeltaNp63 and PCD4, that have been proposed as potential biomarker to predict transforming potential of precancerous lesions and prognosis of well differentiated carcinomas (Ginos et al, 2004;O'Donnell et al, 2005;Saintigny et al, 2009;Arellano-Garcia et al, 2010;Mangone et al, 2010;Reis et al, 2010;Tripathi et al, 2010). However, none of the molecules have had an expression level similar to the findings of present study.…”
Section: Discussioncontrasting
confidence: 56%
“…33 A large number of other significant oncogenic and tumor suppressor targets have been identified for miR-21 in head and neck and other cancers including Ras, programmed cell death 4 (PDCD4), reversion inducing cysteine rich protein with kazal motifs (RECK), and HNRPK. 49,65,[94][95][96] Moreover, Zhang et al 97 suggested that miR-21 could affect formation of reactive oxygen species (ROS) by directly attenuating superoxide dismutase (SOD) family member 3, SOD3, and by an indirect mechanism that limited tumor necrosis factor (TNF)-α production, thereby reducing SOD2 levels to promote tumorigenesis. Likewise, upregulation of miR-24 63 and miR-184 62 is associated with enhanced proliferation and reduced apoptosis.…”
Section: Apoptosis Evasionmentioning
confidence: 99%